Analisis Pengaruh Corporate Governance dan Ukuran Perusahaan terhadap Manajemen Risiko pada Perusahaan di Bursa Efek Indonesia - Arina Juwita; Teddy Jurnali (Global Financial Accounting Journal, 2020)
This investigation means to break down the impact of corporate governance, and company size, on risk management in companies recorded on the Indonesia Stock Exchange. Risk management which is a dummy variable estimated through the presence of a risk management committee will be given an estimation of 1 and in the event that it doesn't have an estimation of 0. The independent variable used is corporate governance by using the proxy proportion of independent directors, board size, audit quality, company size and ownership institutional. This examination utilizes secondary data types, and the total population is 563 companies found on the Indonesia Stock Exchange in 2015 to 2017, where the example was chosen utilizing the purposive sampling method. Logistic regression analysis is a statistical method that will be used in this test. The consequences of this investigation clarify that audit quality has a significant negative effect, institutional ownership and firm size have a significant positive effect on risk management. The proportion of independent directors and the size of the board of commissioners do not affect risk.